Obesitas sentral meningkatkan risiko nyeri punggung bawah pada mahasiswa Program Studi Pendidikan Dokter Universitas Udayana - Carolin, Angelia; Widyadharma, Eka; Sudewi, Raka (E-Jurnal Medika Udayana; Vol 7 No 5 (2018): E-Jurnal Medika Udayana, 2018)
Low back pain (LBP) is a common problem in the community. 70% to 80% of adults have experienced LBP at least once in their lives. LBP is a symptom that causes limitations, ranging from limiting physical activity, decreasing quality of life, to causing psychological distress. There are several things that can cause LBP, one of which is obesity, especially central obesity. Study design using case-control method, this study used 42 respondents who have met the inclusion criteria. Subject respondents are21 students were a group with high risk of LBP and 21 others were low risk group of LBP determined with the Keele START Back Questionnaire. After that, all respondents’ waist circumference were measured. It was found that in the group of people with high risk LBP compared with the high risk LBP group it tended to have central obesity state with proportion (66.7%). In this study a significant relationship between the central obesity with LBP was found (OR: 40, p = 0.02). It can be concluded that central obesity increases the risk of LBP among medical students in Udayana University. The results of this study is expected to be used as the basis for further research and with the existence of these studies the quality of life of medical students will get better. Keywords :Central obesity, low back pain, medical students